Exploring Factors that Contribute to Individual Indebtedness among Young Muslims - Zainol, Zairani; Daud, Zulkiflee; Nizam, Aini Nur Hajjar Khairol; Rashid, Rosemaliza Abd; Alias, Nursiha (International Journal of Economics and Financial Issues, 2016)
This research was aimed at exploring the factors that contribute to individual indebtedness among young Muslims. A total of 350 questionnaires were distributed to the target group within the age range of 25 and 45 years old who are facing debt problems and undergoing financial counselling from AKPK in the Northern region of Malaysia, which encompasses the states of Perak, Pulau Pinang and Kedah/Perlis. Of the 350 questionnaires distributed, 149 were usable as the level of debt of the respondents was 40% and above of the total monthly income. The results revealed that the factors contribute to individual indebtedness are personality extraversion, personality neuroticism, lifestyle impulsive buying, purchasing for lifestyle, parental guidance, religious practice and religious principal. Keywords: Individual Indebtedness, Young Muslims, Factors JEL Classification: M12